Atopic dermatitis – clinical phenotypes and related therapeutic possibilities - Gieroba, Krzysztof; Gładysz, Konrad; Szydłowska, Justyna; Żuchnik, Olga; Król, Olgierd; Kwiatkowski, Piotr; Kuczyńska, Beata; Czelej, Magdalena; Szydłowski, Marcin; Kłos, Aleksander (Journal of Education, Health and Sport, 2022)
Introduction: Atopic dermatitis (AD) is the most common chronic inflammatory skin disease. It is characterized by damaged epidermal barrier, skin dysbiosis and pruritus. It affects up to 20% of the population of developed countries. AD represents a heterogeneous condition belonging to the spectrum of atopic diseases. It occurs in the form of multiple phenotypes with varied pathogenesis requiring different therapeutic strategies. Aim of the study: To summarize the current state of knowledge on AD phenotypes and related therapeutic options. Methods and materials: A review of the literature available in PudMed and Google Scholar databases was conducted. The following keywords were used: "atopic dermatitis", "atopic dermatitis phenotypes", "atopic dermatitis current treatment". Results: There are many phenotypes of AD. However, due to the lack of a consistent classification system, identifying phenotypes is greatly hindered. It is possible to use the division of phenotypes into groups based on age, lesion topography, lesion morphology and patient ethnicity. Various drugs are available for the treatment of AD, but therapeutic strategies for specific phenotypes are sparse and insufficiently understood due to the problem of identifying phenotypes and the complexity of the endotypes behind them. Treatment of AD is not currently based on phenotype-specific targeted therapy. Conclusion: Development of personalized therapy for the treatment of AD requires additional research using uniform definitions of phenotypes and endotypes. It is necessary to create a classification system for AD phenotypes.